Lethal warriors when the new band of brothers came home - Philipps, David (Palgrave Macmillan, 2010)
When the 506th Infantry Regiment--known since World War II as the Band of Brothers--returned to Colorado Springs after their first tour in Iraq, a series of brutal crimes swept through the city. The Band of Brothers had been deployed to the most violent places in Iraq, and some of the soldiers were suffering from what they had seen and done in combat. Without much time to recover, they were sent back to the front lines. After their second tour of duty, the battalion was renamed the Lethal Warriors, and, true to their name, the soldiers once again brought the violence home.